Immortalization and Characterization of Porcine Macrophages That Had Been Transduced with Lentiviral Vectors Encoding the SV40 Large T Antigen and Porcine Telomerase Reverse Transcriptase - Takenouchi, Takato; Kitani, Hiroshi; Suzuki, Shunichi; Nakai, Michiko; Fuchimoto, Dai-ichiro; Tsukimoto, Mitsutoshi; Shinkai, Hiroki; Sato, Mitsuru; Uenishi, Hirohide (Frontiers in Veterinary Science, 2017)
The domestic pig is an important agricultural animal, and thus, infectious diseases that affect pigs can cause severe economic losses in the global swine industry. Various porcine pathogens target macrophages, which are classical innate immune cells. Although macrophages basically protect the host from pathogens, they also seem to contribute to infectious processes. Therefore, cultured macrophages can be used to develop in vitro models for studying not only genes associated with porcine innate immunity, but also the infectious processes of porcine pathogens. However, the availability of porcine macrophage cell lines is limited. In this study, we describe a novel immortalized porcine kidney-derived macrophage (IPKM) cell line, which was generated by transferring the SV40 large T antigen (SV40LT) and porcine telomerase reverse transcriptase (pTERT) genes into primary porcine kidney-derived macrophages using lentiviral vectors. The IPKM displayed a typical macrophage morphology and were routinely passaged (doubling time: about 4 days). These cells were immunostained for macrophage markers. In addition, they exhibited substantial phagocytosis of polystyrene microbeads and released inflammatory cytokines upon lipopolysaccharide (LPS) stimulation. Furthermore, the maturation and secretion of interleukin-1b were observed after nigericin-induced inflammasome activation in LPS-primed IPKM. These findings suggest that IPKM exhibit the typical inflammatory characteristics of macrophages. By transferring the SV40LT and pTERT genes using lentiviral vectors, we also successfully immortalized macrophages derived from the peripheral blood of a low-density lipoprotein receptor-deficient pig. These results suggest that the co-expression of SV40LT and pTERT is an effective way of immortalizing porcine macrophages.